2003
DOI: 10.1046/j.1341-8076.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hemangioma presenting as pseudo–Meigs’ syndrome with elevated CA125

Abstract: We report the first case of ovarian hemangioma presenting as pseudo-Meigs' syndrome with elevated CA125. Abdominopelvic computed tomography (CT) assumed ovarian carcinoma. Chest CT revealed pleural effusion. Intraoperative frozen-section examination of the right ovary showed benign hemangioma. After operation, chest radiograph and ultrasonography showed no pleural effusion or ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Studies have shown Meigs may also present with a fourth component: an increase in serum CA-125 (25)(26)(27)(28)(29). Although not formally recognized as a Meigs syndrome neoplasm, hemangioma of the ovary has manifested similarly as a solitary ovarian tumor, ascites, and pleural effusion in 2 patients (3,5). The clinical spectrum of Meigs, particularly with the inclusion of CA-125, overlaps with a recurrent presentation or triad in some patients with ovarian hemangioma: a benign ovarian tumor, increased CA-125 (usually in the hundreds), and massive ascites.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have shown Meigs may also present with a fourth component: an increase in serum CA-125 (25)(26)(27)(28)(29). Although not formally recognized as a Meigs syndrome neoplasm, hemangioma of the ovary has manifested similarly as a solitary ovarian tumor, ascites, and pleural effusion in 2 patients (3,5). The clinical spectrum of Meigs, particularly with the inclusion of CA-125, overlaps with a recurrent presentation or triad in some patients with ovarian hemangioma: a benign ovarian tumor, increased CA-125 (usually in the hundreds), and massive ascites.…”
Section: Discussionmentioning
confidence: 97%
“…Hemangiomas are a component of numerous syndromes, but, to date, ovarian hemangiomas have only been associated with Kasabach-Merritt syndrome (20,21), pseudo-Meigs syndrome (3,5), and an unnamed triad of unilateral or bilateral hemangioma, CA-125 elevation, and massive ascites (2)(3)(4)(5). Kasabach-Merritt (also known as hemangioma with thrombocytopenia) presents as a vascular tumor and consumptive thrombocytopenia or coagulopathy that can lead to fatal internal bleeding (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8,9 Some of the complications of ovarian haemangioma can be listed as pseudo-Meigs syndrome, 10 stromal leutinization, 11 stromal hyperplasia and thrombocytopenia. 1,3 Histopathogenesis of ovarian haemangioma is topic of debate with many theories coming up.…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated serum CA125 has been reported in various cases of pseudo-Meigs' syndrome associated with metastatic ovarian cancer [9], ovarian benign tumors such as struma ovarii [10], hemangioma [11] and germ cell tumor [6], uteral [12] and renal tumor [13]), and collagen vascular disease simulating pseudo-Meigs' syndrome [14]. Thus, elevated CA125 has to be interpreted with caution in managing relevant patients.…”
Section: Discussionmentioning
confidence: 99%